Localizing the seizure onset zone by comparing patient postictal hypoperfusion to healthy controls. Issue 8 (1st June 2020) - Perera, Tefani; Gaxiola‐Valdez, Ismael; Singh, Shaily; Peedicail, Joseph; Sandy, Sherry; Lebel, R. Marc; Li, Emmy; Milne‐Ives, Madison; Szostakiwskyj, Jessie; Federico, Paolo; ,
Abstract: Arterial spin labeling (ASL) MRI can provide seizure onset zone (SOZ) localizing information in up to 80% of patients. Clinical implementation of this technique is limited by the need to obtain two scans per patient: a postictal scan that is subtracted from an interictal scan. We aimed to determine whether it is possible to limit the number of ASL scans to one per patient by comparing patient postictal ASL scans to baseline scans of 100 healthy controls. Eighteen patients aged 20–55 years underwent ASL MRI <90 min after a seizure and during the interictal period. Each postictal cerebral blood flow (CBF) map was statistically compared to average baseline CBF maps from 100 healthy controls (pvcASL; patient postictal CBF vs. control baseline CBF). The pvcASL maps were compared to subtraction ASL maps (sASL; patient baseline CBF minus patient postictal CBF). Postictal CBF reductions from pvcASL and sASL maps were seen in 17 of 18 (94.4%) and 14 of 18 (77.8%) patients, respectively. Maximal postictal hypoperfusion seen in pvcASL and sASL maps was concordant with the SOZ in 10 of 17 (59%) and 12 of 14 (86%) patients, respectively. In seven patients, both pvcASL and sASL maps showed similar results. In two patients, sASL showed no significant hypoperfusion, while pvcASL showed significant hypoperfusion concordant with the SOZ. We conclude that pvcASL is clinically useful and although it may have a lower overall concordance rate than sASL, pvcASL does provide localizing or lateralizing information for specific cases that would be otherwise missed through sASL. Abstract : We compared post‐ictal hypoperfusion ASL MRI data in epilepsy patients to healthy controls to determine the location of the seizure onset zone (SOZ). This comparison identified the clinically suspected SOZ in 59% of patients. These findings matched our previous subtraction ASL MRI study (Gaxiola‐Valdez et al., 2017).